The psychotherapy documentation primer - Wiger, Donald E., 1953- (Hoboken, NJ : Wiley, 2011)
'Fully updated to reflect the latest practice and reporting requirements, The Psychotherapy Documentation Primer, Third Edition is the benchmark record-keeping reference for working mental health professionals. It demystifies the entire documentation process and includes everything a therapist needs to know to record client intake, treatment, and progress. New chapters are included on the art and science of psychological assessment and treatment, and ethical considerations in documentation. Mental health practitioners and graduate students will find the latest information on regulations affecting managed care, accrediting agencies, and the government'--
Machine generated contents note: Chapter 1 IntroductionChapter 2 The Art and Science of Psychological Assessment and TreatmentChapter 3 Overview of Current Documentation Procedures and Third Party RequirementsChapter 4 Ethical Considerations in DocumentationChapter 5 The Biopsychosocial AssessmentChapter 6 The Mental Status ExamChapter 7 Validating a DiagnosisChapter 8 Formulating a Treatment PlanChapter 9 Writing Progress NotesChapter 10 Documenting the Need for Additional ServicesAppendix A Putting it all Together: Documented Chart for Mental Health ServicesAppendix B Overview of Outcome MeasuresAppendix C Overview of HIPAA Guidelines in Mental Health SettingsGlossaryReferences.
Includes index.
Keywords: Psychiatric records; Mental health services -- Medical records; Mental health services -- Management; PSYCHOLOGY / Psychotherapy / General